To rewrite the equation \( \frac{4x}{3x - 12} + 3 = 10 \) in two equations joined by "and," we first isolate the fraction:
-
Start with the original equation: \[ \frac{4x}{3x - 12} + 3 = 10 \]
-
Subtract 3 from both sides: \[ \frac{4x}{3x - 12} = 10 - 3 \] \[ \frac{4x}{3x - 12} = 7 \]
Now we can express this as two equations joined by "and":
-
The first equation represents the fraction: \[ \frac{4x}{3x - 12} = 7 \]
-
The second equation represents the rearranged equation: \[ 10 - 3 = 7 \]
Putting it together, we write: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 10 - 3 = 7 \]